Modeling and optimization of a high-pressure ethylene polymerization reactor using gPROMS - Asteasuain, Mariano (2008)
A gPROMS implementation of a comprehensive steady-state model of the high-pressure polymerization of ethylene in a tubular reactor is presented. Model outputs along the reactor length include the complete molecular weight distribution and branching indexes, as well as monomer conversion, average molecular weights, reactants’ compositions, and reactor temperature and pressure. A detailed calculation of physical and transport properties, such as the reaction mixture density, heat-transfer capacity, viscosity and global heat-transfer coefficient is also included. The reactor model is included in an optimization framework that is used to determine the best operating conditions for producing a polymer with tailor-made molecular structure in terms of the complete molecular weight distribution, branching and polydispersity.